Maimonides' confrontation with mysticism - Kellner, Menachem Marc, 1946- (Littman library of Jewish civilization (Series), 2006)
"This book takes issue with the widespread assumption that Maimonides famous Thirteen Principles are the last word in Orthodox Jewish theology. The author shows that numerous traditional theologians in the last 900 years have in fact taken issue with Maimonides principles, both in their details as well as with regard to certain fundamental points in Maimonides' formulation." "Many books on Maimonides have been written and still more will appear. Few present Maimonides, as Menachem Kellner does, against the actual religious background that informed his many innovative and influential choices. Kellner not only analyses the thought of the great religious thinker but contextualizes it in terms of what he calls the 'proto-kabbalistic' Judaism that preceded him. Kellner shows how the Judaism that Maimonides knew had come to conceptualize the world as an enchanted universe, governed by occult affinities. He shows why Maimonides rejected this and how he went about doing it. Kellner argues that Maimonides' attempted reformation failed, the clearest proof of that being the success of the kabbalistic counter-reformation which his writings provoked." "Kellner shows how Maimonides rethought Judaism in different ways. It is in highlighting this process and identifying Maimonides as a religious reformer that this book makes its key contribution. Maimonides created a new Judaism, 'disenchanted', depersonalized, and challenging; a religion that is at the same time elitist and universalist."--Jacket